2016
DOI: 10.1007/s00213-016-4247-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic vocalization in rats self-administering heroin and cocaine in different settings: evidence of substance-specific interactions between drug and setting

Abstract: RationaleClinical and preclinical evidence indicates that the setting of drug use affects drug reward in a substance-specific manner. Heroin and cocaine co-abusers, for example, indicated distinct settings for the two drugs: heroin being used preferentially at home and cocaine preferentially outside the home. Similar results were obtained in rats that were given the opportunity to self-administer intravenously both heroin and cocaine.ObjectivesThe goal of the present study was to investigate the possibility th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 63 publications
3
16
0
Order By: Relevance
“…This suggests that the presence of a peer is not stressful, but rather reinforcing. Since it has been shown that cocaine by itself can induce the emission of positive USV (Avvisati et al, 2016), our results confirm that increased USV emissions here are more related to the presence of a peer than to cocaine itself.…”
Section: Is Social Presence a Stressor?supporting
confidence: 87%
“…This suggests that the presence of a peer is not stressful, but rather reinforcing. Since it has been shown that cocaine by itself can induce the emission of positive USV (Avvisati et al, 2016), our results confirm that increased USV emissions here are more related to the presence of a peer than to cocaine itself.…”
Section: Is Social Presence a Stressor?supporting
confidence: 87%
“…Although the functional significance of these differences remains to be fully explored, they might have implications for both research and treatment. It is remarkable, for example, that the functional or anatomic integrity of the dopaminergic system is required for the reinforcing properties of cocaine but not of heroin (Ettenberg et al, 1982;Pettit et al, 1984;Pisanu et al, 2015), that distinct projections from the PFC to the shell of the NAcc are implicated in the relapse to cocaine versus heroin seeking after abstinence (Peters et al, 2008;Bossert et al, 2012), and that basic environmental manipulations gate in opposite directions the reinforcing, affective, and neurobiological responses to heroin versus cocaine in rats and humans (Uslaner et al, 2001;Ferguson et al, 2004;Caprioli et al, 2007aCaprioli et al, , 2008Caprioli et al, , 2009Paolone et al, 2007;Celentano et al, 2009;Montanari et al, 2015;Avvisati et al, 2016;De Pirro et al, 2018;De Luca et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In support of context facilitating in part the positive response following cocaine administration, a recent report showed that rats for whom the self-administration context was distinguished (i.e. Non-Resident) emitted significantly greater 50-kHz USVs during cocaine self-administration relative to Resident rats (Avvisati et al , 2016). These prior reports and our current findings support that psychostimulant-paired contexts elicit a strong subjectively-positive anticipatory response.…”
Section: Discussionmentioning
confidence: 99%